Mergers and acquisitions in the telecommunications industry: Form an Asia Pacific perspective - Ahmad Warraich (2008)
This dissertation focuses on the reasons for the continued attractiveness of M&A in the telecommunications industry, points out the main objectives of M&A activity in the telecommunications industry as set out by the company’s Chairperson or CEO, and reviews various studies by M&A experts on the challenges and success factors of M&A.